2013
DOI: 10.1111/cico.12015
|View full text |Cite
|
Sign up to set email alerts
|

Do Affordable Housing Projects Harm Suburban Communities? Crime, Property Values, and Taxes in Mount Laurel, NJ

Abstract: This paper offers a mixed-method analysis of the municipal-level consequences of an affordable housing development built in suburban New Jersey. Opponents of affordable housing development often suggest that creating affordable housing will harm surrounding communities. Feared consequences include increases in crime, declining property values, and rising taxes. To evaluate these claims, the paper uses the case of Mt. Laurel, NJ – the site of a landmark affordable housing legal case and subsequent affordable ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…The American Academy of Pediatrics and other national health organizations have called for the development and evaluation of interventions that directly target the social determinants underlying child health disparities. 1–4 Given a large and consistent literature revealing a clear link between housing and health, 5 housing assistance programs (ie, publicly-supported housing subsidies subject to ongoing public debate 6,7 and budgetary threat 8–11 ) might play an important role in promoting the health of disadvantaged children. 12,13…”
mentioning
confidence: 99%
“…The American Academy of Pediatrics and other national health organizations have called for the development and evaluation of interventions that directly target the social determinants underlying child health disparities. 1–4 Given a large and consistent literature revealing a clear link between housing and health, 5 housing assistance programs (ie, publicly-supported housing subsidies subject to ongoing public debate 6,7 and budgetary threat 8–11 ) might play an important role in promoting the health of disadvantaged children. 12,13…”
mentioning
confidence: 99%
“…The LIHTC was not initially designed to reduce CAN rates, but other studies have shown that policies that improve housing conditions, such as LIHTC and other inclusionary housing policies, remain promising strategies to reduce violence and injury risk (Albright et al, 2013; Freedman & Owens, 2011). While we did not find a significant association between the number of LIHTC units and CAN, it is possible that the LIHTC has a more nuanced, indirect effect on CAN not measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, poverty rates have been found to decline in high-poverty neighborhoods after the completion of LIHTC developments, and in general, there is little evidence that the LIHTC program contributes to poverty concentration or residential segregation (Ellen, Horn, & O’Regan, 2016; Freedman & McGavock, 2015; Horn & O’Regan, 2011). There are mixed findings regarding the impact of affordable housing on the stability of the surrounding community, but generally, associations between subsidized housing developments and neighborhood crime are weak or insignificant, suggesting that some concerns about affordable housing may be misguided (Albright et al, 2013; Ellen, Lens, & O’Regan, 2012; Freedman & Owens, 2011; Lens, 2014). In fact, one study demonstrated that LIHTC developments built in the poorest neighborhoods resulted in significant reductions in violent crime, but not property crime (Freedman & Owens, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main trend in current research in this field focuses on the links among the neo-liberal economy, widening socio-spatial gaps, the creation of urban borders, the eradication of public space and intensifying city violence (Caldeira, 1996; Davis, 1992). Some other scholars, who have also depicted the link between city polarization and the militarization of the crime world (Wacquant, 2008), perceive crime as a relationship that portrays national, ethnic and social class struggle (Albright et al, 2013; Ilan, 2011). The spatial manifestation of criminal activity as a specific hotspot is thus inherently associated with the ways in which urban space is divided up by different borders.…”
Section: Theoretical Backgroundmentioning
confidence: 99%